Anti-war and anti-draft protest - Spartan Daily:::Creator::::::::::::
Anti-war and anti-draft student protest. In this view, three students are eating ice cream cones while listening to two other students. Posters announcing a student strike for peace event are situated between the seated student. A large peace symbol is prominent on the poster on the left, and to the right, a mock oversized poster reads: "Selective Service System Certificate," with "Resist April 29, 1968," written across the certificate.